Novel Surrogate Measures Based on a Similarity Network for Neural Architecture Search - Kuş, Zeki; Akkan, Can; Gülcü, Ayla (IEEE, 2023)
We propose two novel surrogate measures to predict the validation accuracy of the classification produced by a given neural architecture, thus eliminating the need to train it, in order to speed up neural architecture search (NAS). The surrogate measures are based on a solution similarity network, where distance between solutions is measured using the binary encoding of some graph sub-components of the neural architectures. These surrogate measures are implemented within local search and differential evolution algorithms and tested on NAS-Bench-101 and NAS-Bench-301 datasets. The results show that the performance of the similarity-network-based predictors, as measured by correlation between predicted and true accuracy values, are comparable to the state-of-the-art predictors in the literature, however they are significantly faster in achieving these high correlation values for NAS-Bench-101. Furthermore, in some cases, the use of these predictors significantly improves the search performance of the equivalent algorithm (differential evolution or local search) that does not use the predictor.
Keywords: Neural Architecture Search; Surrogate Model; Similarity-Based Prediction; Evolutionary Algorithm